Implementasi Teori Hukum Pembangunan Mochtar Kusumaatmadja dalam Aspek Digitalisasi Pelayanan Publik - Fakhruddin Al-Ghiffari (Jurnal Hukum Lex Generalis, 2025)
Digitalization of public services is a crucial step in achieving good governance and fostering an inclusive, effective, accountable, and transparent government, particularly in the modern era. The government has shown its commitment to public service digitalization by issuing Peraturan Presiden Republik Indonesia Nomor 82 Tahun 2023 tentang Percepatan Transformasi Digital dan Keterpaduan Layanan Digital Nasional. This regulation aims to establish high-quality and reliable public services, an electronic-based government system, and an integrated One Data Indonesia system. Additionally, the government issued Peraturan Presiden Republik Indonesia Nomor 95 Tahun 2018 tentang Sistem Pemerintahan Berbasis Elektronik (SPBE), reflecting its effort to accelerate governance using updated information technology (e-government). According to Mochtar Kusumaatmadja, law serves not only to maintain order but also as an instrument for driving change toward a modern, dynamic, and advanced society. By applying the concept of law as a tool for development, societal values can evolve based on positive attitudes and modern perspectives. In the context of public service, the government’s primary focus should extend beyond technology and infrastructure to include enhancing human resource quality within government institutions. Such development must align with good values and modern thinking to ensure the effectiveness of digitalized services